TANGGUNG JAWAB HUKUM APARATUR SIPIL NEGARA BERKAITAN DENGAN INDISIPLINER KERJA BERDASARKAN UU No. 5 TAHUN 2014 DI KABUPATEN KUTAI BARAT - Rizeldy Faschalis (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTBureaucracy reform is essentially an effort to make fundamental reforms and changes to the system of governance, especially concerning aspects of institutional (organization), management and human resources of the state apparatus. Various problems or obstacles that result in the system of governance is not expected to run properly should be reorganized or updated. Bureaucracy reform is implemented in order to realize good governance. In other words, bureaucratic reform is a strategic step to build the state apparatus to be more efficient and effective in carrying out the general duties of government and national development